The concept of the landscape and its acceptance in the practice - Miklós, László (Acta Geographica Debrecina Landscape & Environment series, 2012)
The landscape is historically perceived basically in two ways: as a tangible material reality and also as an intangible, mental and artistic experience. The basic practical policies related to the landscape ecology under the umbrella conception of the integrated land resources management are based on materialistic geocomplex/geosystem conception. In last decades a massive wave of the “friends of landscape” appeared, who shifted their attendance to the cultural-historical-value and perception based approach to the landscape. This wave is supported by the compromiss soft definition of the landscape and the wording of the European Landscape Convention. Nevertheless, the penetration of the landscape to the practical policies requires the materialistic approach and definition of the landscape.